PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DENGAN BERBANTUAN MEDIA PEMBELAJARAN PAPAN PINTAR PANCASILA UNTUK MENINGKATKAN KEAKTIFAN PESERTA DIDIK KELAS I SDN PODOREJO 02 - Arini Widi Utami; Irine Amalia Sinta Balqis; Susilo Tri Widodo; Nur Indah Wahyuni; Kunti Rohmah (STKIP Subang, 2023)
This research aims to find out whether the application of the NHT learning model can increase the active participation of class 1 students at SDN Podorejo 02 in learning activities. The research method used is quantitative descriptive, namely a type of research that describes variables as they are, supported by data in the form of numbers generated from the actual situation. Data collection techniques were carried out using unstructured interviews with class teachers and observation. The results of the research resulted in the application of the NHT-type cooperative learning model which can increase students' active participation in learning. At the first meeting, the active presentation of students was 72% which was in the good classification and at the second meeting it increased to 86% which was in the very good classification.